RISIKO RIWAYAT KELUARGA DAN PENGGUNAAN ALAT KONTRASEPSI HORMONAL TERHADAP KANKER PAYUDARA DI RSD dr. SOEBANDI JEMBER - Nelyta Oktavianisya (STRADA : Jurnal Ilmiah Kesehatan, 2013)
Breast cancer is a malignant derived from cells in the breast. The disease of breast cancer is one of cancer disease killers of women. Some research shows that there are influence between usage of hormonal contraceptives and breast cancer. Purpose of this research is to analyze rist factor of family history and hormonal contraception us to breast cancer in dr. Soebandi Jember Hospital. This research was analytical study using case control design. The samples were 44 woman suffering from breast cancer and 88 woman without breast cancer. The data obtained were presented in table form and analyzed using univariable, bivariable with Chi-square test, and multivariable analysis with logistic regression test with significance level of 5% (α=0.05). The research result were the hormonal contraceptive that was used was pill type, length of use of contraceptive methods and family history affected on the breast cancer. Prevention efforts that can be done by dr. Soebandi Jember Hospital is an increase in health promotion and screening, especially for women with a family history of breast cancer in the selection and proper use of contraceptives.